PERLINDUNGAN HUKUM TERHADAP SAKSI DAN KORBAN PENCABULAN MENURUT UU NO 31 TAHUN 2014 - Putri, Wirda Ayu; Qorib, Fathul (STIH Zainul Hasan Kraksaan Kraksaan, 2024)
Abstract Protection for witnesses and victims is a form of government in protecting or providing security for witnesses and victims before and after giving testimony in a criminal case that they have seen and experienced themselves. Meanwhile, fornication is any type of act that violates decency and decency or can also be a vile act that falls within the realm of lust, such as touching the genitals, kissing, touching the breasts and so on. Researchers are required to understand the principles in the applicable laws and regulations that have been established in addition to using a conceptual approach so that in this writing they can be found in the laws. The results of this research show that: (a) Legal protection is an illustration of the working of the legal function to realize legal goals, namely justice. Benefits and legal certainty. Legal protection is protection given to legal subjects in accordance with legal regulations, both in the form of preventive (prevention) and in the form of recessive (coercion), both written and unwritten in the context of enforcing legal regulations. (b) The form of legal protection for witnesses and victims is the view of citizens or society that in a government regulation there must be protection for every person who provides information for the purpose of investigation. Based on the above, this research recommends: The government and the authorities in providing protection services to witnesses and victims, especially victims of sexual abuse, need to consider stricter and more effective protection services provided to witnesses and victims of sexual abuse. Keywords: Obscenity, Legal Protection, Witnesses and Victims.